Transcriptional landscape of rice roots at the single-cell resolution - Liu, Qing; Liang, Zhe; Feng, Dan; Jiang, Sanjie; Wang, Yifan; Du, Zhuoying; Li, Ruoxi; Hu, Guihua; Zhang, Pingxian; Ma, Yanfei; Lohmann, Jan U.; Gu, Xiaofeng (Molecular plant, 2021)
There are two main types of root systems in flowering plants, namely taproot systems of dicots and fibrous root systems found in monocots. Despite this fundamental split, our current knowledge of cellular and molecular mechanism driving root development is mainly based on studies of the dicot model Arabidopsis. However, the world major crops are monocots and little is known about the transcriptional programs underlying cell-type specification in this clade. Here, we report the transcriptomes of more than 20 000 single cells derived from root tips of two agronomically important rice cultivars. Using combined computational and experimental analyses we were able to robustly identify most of the major cell types and define novel cell-type-specific marker genes for both cultivars. Importantly, we found divergent cell types associated with specific regulatory programs, including phytohormone biosynthesis, signaling, and response, which were well conserved between the two rice cultivars. In addition, we detected substantial differences between the cell-type transcript profiles of Arabidopsis and rice. These species-specific features emphasize the importance of analyzing tissues across diverse model species, including rice. Taken together, our study provides insight into the transcriptomic landscape of major cell types of rice root tip at single-cell resolution and opens new avenues to study cell-type specification, function, and evolution in plants.